Morphological Study of Electrospun Polyvinylpyrrolidone Fibers at High Concentration Using Water and Ethanol Solvents - Nugroho, Doni Bowo; Kamal, Nada Nadzira Ayasha; Sidabalok, Jenni Bunga Enjelita; Wati, Rosita; Resfita, Nova; Gifari, Muhammad Wildan (Journal of Energy, Material, and Instrumentation Technology, 2025)
Polyvinylpyrrolidone (PVP) is widely used in biomedical applications, and electrospinning is a common method for fabricating PVP nanofibers. While most studies focus on low to moderate concentrations (5–12 wt%), this work investigates the electrospinning of high-concentration PVP solutions, 50% (m/v), using distilled water and ethanol under applied voltages of 8 and 12 kV. Fiber morphology was characterized by scanning electron microscopy (SEM) and diameter distributions analyzed with ImageJ. Results showed that water-based solutions produced discontinuous fibers with ribbons, beads, and film-like structures, while ethanol-based solutions formed irregular fiber networks at 8 kV but transformed into globular particles at 12 kV due to jet instability. Diameter distribution of water-based fibers was broader (0.31–1.83 µm), whereas ethanol-based fibers exhibited a narrower but larger range (1.29–3.54 µm). These findings indicate that excessive polymer concentration leads to unstable structures, contrasting with continuous fibers reported at lower concentrations. The study highlights the limitations of electrospinning PVP at high concentrations and suggests potential applications in porous films and drug-release systems rather than uniform nanofibers.